Redes sociais e bibliotecas: adapte-se ou fique fora do jogo - Siqueira, Thiago Giordano de Souza (Brasil, 2020)
A large number of libraries use or could use social networks to advertise their services and interact with their public. Practical possibilities of using social networks to form communities and interact with users are presented considering the scenario where Brazilians stay more than nine hours connected daily, therefore social networks are a powerful source of communication.